Special Economic Zones and Industrial Parks in South Asia : An Assessment of Their Regulatory Structures - Galal, Rami (World Bank, Washington, DC, 2021)
This paper reviews the policies and regulations for special economic zones and other spatial development modalities in the countries within proximity of the Eastern Corridor in South Asia, and it assesses whether those policies and regulations are effectively designed. The assessment finds mixed results. On the positive side, governments in these countries exhibit a strong political commitment to the zones’ success, providing them with dedicated policies of both fiscal incentives and regulatory concessions, combined with administrative simplification to help zone developers and tenant enterprises. However, these arrangements include some notable shortfalls. For example, some incentives are inconsistent with the zone objectives, violate some international regulations, or miss necessary business facilitation measures. Moreover, there is no mechanism to evaluate the effectiveness and cost-efficiency of different incentives. Zone tenancy requirements are not always well specified, feasible, or consistent with zone objectives. As for the regulatory and institutional structures of zone programs, there are some common shortfalls, especially in terms of (a) clarity of zone objectives, (b) the roles of different agents, (c) the autonomy and inclusivity of those agents, and (d) the agents’ authority to carry out their responsibilities, and there are some shortfalls in the resources that agents need to manage operations effectively. To maximize the benefits from these zones, governments of the region could adopt reforms to ensure that incentives and tenancy requirements are aligned with zone objectives and that regulatory frameworks are clear, fair, and effective.